The Effect of Strategic Containment on Organizational Brilliance : An Analytical Research in Ur State Company - Kadhim Zrar, Ibtisam; Abd Al Wadud Al-Abbasi, Adel (Journal of Economics and Administrative Sciences, 2024)
The current research aims to demonstrate the relationship and impact between strategic containment and its dimensions (adopting alternatives, facilitating adaptability, synthesizing information, and implementing the chosen strategy) on organizational brilliance and its dimensions (brilliance in leadership, brilliance in service and innovation, and brilliance in Knowledge) in the Ur State Company. The research problem question was whether top management in the organization practices the strategic containment process or not, and does it affect organizational brilliance? The sample of the research consisted of middle management managers (120) participants. To analyze data and information and test hypotheses, the research used many statistical methods such as standard deviation, coefficient of variation, arithmetic mean, and simple regression coefficient by the statistical program (SPSS V26). The most obvious result of the research is that strategic containment and its dimensions totally and individually affect the variable organizational brilliance directly. Also, there is a lack of clarity in explaining the details of ongoing innovations and how to achieve outstanding performance, which negatively affects employees’ understanding, and then the researched company cannot achieve organizational brilliance. Research type: Research paper